Today's Youth, Tomorrow's Leaders: How Parents and Educators Can Influence and Guide the Learning Process - Guha, Smita (Rowman & Littlefield Publishers, 2013)
Today’s Youth, Tomorrow’s Leaders is for parents, teachers, caregivers, directors, educators, administrators and all who work with children to encourage learning. This book has examples of effective practices in early childhood education from different countries worldwide. This book will emphasize the different ways that adults can make difference in the lives of children so that today’s children will be well nurtured and will become effective citizens in future. The structure of the book is adapted to the new Early Childhood Common Core. The book has case studies, illustrations, pictures, and tables to help the readers. Each chapter will also have a summary at the end with discussion questions.